Observations on anthropological research concerning the period of Hungarian conquest and the Arpadian age - Szathmáry, László (Acta Biologica Szegediensis, 2000)
The present paper is aimed at providing a summary of the contributions of anthropological research into the Carpathian Basin history of the 10th-13th century ancient Hungarians relying on the strength of anatomical, demographical and sociological database. Special attention is paid to the moments in population development which proved to have diverged during the pagan era (10th century) and the early Christian era (11th-13th century).